TRANSFORMASI ARTISTIK: DINAMIKA DESAIN BATIK DALAM KONTEKS SOSIAL-BUDAYA MODERN - Zuhro, Aida (AKSA: Jurnal Desain Komunikasi Visual, 2024)
This study examines the design trends of batik motifs in Indonesia over the past five years, highlighting how the evolution of these designs has been influenced by technological factors, changing consumer preferences, and cultural preservation efforts. By analyzing nature-inspired designs, the use of digital technology in the creative process, and the trend towards more minimalist and contemporary designs, the study reveals how batik remains relevant and evolves as a dynamic form of cultural expression. The integration of traditional elements and modern innovations creates batik motifs that are not only aesthetically appealing but also rich in cultural and historical value. The results show that batik is an important example of the adaptation of tradition in a modern context, demonstrating a unique ability to maintain its cultural essence while remaining responsive to changing times.